The Influence of Transformational Leadership Style and Work Motivation on Employee Performance at Ace Hardware Balubur Town Square - Taufan, Aliftia; Rahayu, Muji (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to examine the influence of transformational leadership style and motivation on employee performance. The research employs a quantitative approach with data collection conducted through questionnaires. The population of the study consists of employees of Ace Hardware at Balubur Town Square. The sampling technique used is non-probability sampling with a saturated sampling method. Data analysis is performed using multiple regression analysis. Partial hypothesis testing results indicate that transformational leadership style has a negative and significant influence on employee performance, while motivation has a positive and significant influence on employee performance. Simultaneous hypothesis testing shows that both transformational leadership style and motivation have a significant influence on employee performance together.